Magnetic phase transition in valence tautomers as polymorphs of 3-iodolawsone: Single crystal X-ray structure, DSC and EPR studies - Zaware, Santosh B.; Dagade-Waghmode, Shobha; Gonnade, Rajesh G.; Srinivas, Darbha; Rane, Sandhya Y. (Journal of Molecular Structure, 2009)
Three polymorphs of 3-iodolawsone (I-III) have been isolated and characterized by single crystal X-ray diffraction, electron paramagnetic resonance (EPR) spectroscopy and differential scanning calorimetry (DSC) techniques. Polymorphs I and II were crystallized from methanol in two different valence tautomeric forms: hydroxynaphthoquinone (HNQ) and hydroxynaphthoseimquinone (HNSQ) as needles and thick plates, respectively. Polymorph III was crystallized from ethanol in HNQ form, as thin plates Chiral crystals of I belongs to the orthorhombic P2(1)2(1)2(1) space group: II and III belong to the monochnic non-centrosymmetric space group Cc. The molecules are packed via O-H O bonding and pi . pi stacking interactions. The study reveals that relatively stronger intermolecular H-bonding (2.02 angstrom) and most favoured pi . pi stacking (similar to 3 49 angstrom) interactions lead II to HNSQ radicals, presence of which was confirmed by EPR (g = 2.0052) spectroscopy. Interestingly, these materials exhibit crystal-to-crystal magnetic phase transition from polymorph I (diamagnetic) to polymorph II (paramagnetic structure) at 171.1 degrees C as identified by DSC and X-ray crystallographic studies (C) 2009 Elsevier B.V. All rights reserved
Keywords: 3-Iodolawsone; Hydroxynaphthoquinone (HNQ); Hydroxynaphthosemiquinone radical (HNSQ); Magnetic phase transition; Polymorphs; Valence tautomers

Crystal structure, NMR and theoretical investigations on 2-(o-hydroxy-anilino)-1,4-napthoquinone - Feizi, Nourollah; Pinjari, Rahul V.; Gejji, Shridhar P.; Sayyed, Fareed B.; Gonnade, Rajesh G.; Rane, Sandhya Y. (Journal of Molecular Structure, 2010)
Crystal structure, (1)H NMR and cyclic voltammetric investigations of 2-(o-hydroxy-anilino)-1,4-napthoquinone (HAN), resulting from coupling of aminophenol with 2-hydroxy-1,4-napthoquinone, have been carried out. X-ray structure reveals that the HAN ligand crystallizes in orthorhombic space group Pca2(1) with Z = 4. forming a chain via inter-molecular O2 center dot center dot center dot H1A-O1 and C15-H15 center dot center dot center dot O3 interactions. Both (1)H NMR and cyclic voltammetry experiments suggest the titled ligand is associated and exists as dinner in d(6)-DMSO while the monomer has been predicted in CDCl(3) solution. Density functional calculations can be utilized to gauge the strength of hydrogen-bonded interactions from the (1)H chemical shifts in the NMR spectra. Self-consistent reaction field (SCRF) calculations further support the inferences drawn from cyclic voltammetry experiments. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: (1)H NMR; cyclic voltammetry; Density functional; hydrogen bonding; Napthoquinone

Structure-function mimicry of oxidized purple acid phosphatase-PAP(ox)-A new functional model - Waghmode, Shobha A.; Date, Sadgopal K.; Gupta, Vidya S.; Rane, Sandhya Y. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2010)
{Electronic structure and spectroscopic properties of the novel diiron active site of oxidized mammalian purple acid phosphatase analogues, Fe-6: [Fe-2 (mu-O) (mu-OAc) (4HNSQ(ox))(2 center dot-)(ONSQ(ox))(2 center dot-)(H2O)(4)] and Fe-7: [Fe-2 (mu-O) (mu-OAc)(ONSQ(ox))(2 center dot-)(OAc) (H2O)(4)] are described. Magnetic susceptibility SQUID data of Fe-6 are best fitted to Heisenberg's isotropic spin pair (S = 5/2, 3/2) model using magnetic parameters g = 2 and J = - 36.8 cm(-1) with R factor = 6.4 x 10(-4). The antiferromagnetic exchange establishes Fe(III)-O-Fe(III) dimeric core with Fe(III) site having two radical ligations in the naphthosemiquinone oxime form of lawsone oxime. In the model compound Fe-7 of oxidized purple acid phosphatase, bridged and terminal acetate functions are identified according to their different energies of activations, i.e, similar to 34 and 58 kJ mol(-1) respectively. Also, the reduced naphthoquinone oxime form of ligand is characterized by its energy of activation (similar to 15 kJ mol(-1)) from pyrolytic reaction. Mossbauer parameters
Keywords: Antiferromagnetic exchange; Bioinorganic chemistry; DNA cleavage; iron; Nuclease activity; PAP(ox) analogues

Antioxidant and anticancer activities of supramolecularly controlled magnetostructural halo-oximes of lawsone - Zaware, Santosh B.; Gonnade, Rajesh G.; Srinivas, Darbha; Khan, Ayesha A.; Rane, Sandhya Y. (New Journal of Chemistry, 2011)
Crystal engineering based on halogen bonding together with host-guest interactions of water molecules via H-bonding, stabilizing supramolecular architecture in chloro 1, bromo 2 and iodo 3 oximes of lawsone, is discussed. 1 and 2 crystallize in orthorhombic, non-centrosymmetric space group Pna2(1) while 3 crystallizes in monoclinic P2(1)/n space group. Non-covalent competitive interactions of asymmetric solvation and halogen bonding can have a large influence on the spin distribution in 1, 2 and 3 derivatives of spin carrier lawsone live polymer as revealed by single crystal X-ray and EPR studies. The significant C3-Cl/Br center dot center dot center dot O, C3-Cl/Br center dot center dot center dot H, O-H center dot center dot center dot O-C, C-H center dot center dot center dot pi and pi center dot center dot center dot pi interactions have been identified in the molecular assemblies leading to net magnetostructures of halo-oximes. Dimer-of-dimer-type tetrameric radical assembly of 3 and interacting bi- and monoradical chain on 2(1) axis in 1 and 2 have been identified. The proton-coupled electron transfers possibly govern the antioxidant nature in halooximes of spin carrier lawsone in terms of oxygen reduction to water molecules. Such activity is found to be directly proportional to the spin (radical) concentrations in 1 to 3 and increases in order 1 < 2 < 3 according to halogen bonding effect. The antioxidant chemical DPPH assays for scavenging of such free radicals result in similar trend of increasing order like 1 < 2 < 3, but the chemical in vitro as well as ex vivo SOD antioxidant activities and biological anticancer activity on MCF-7, Hela and HL-60 cell lines show the increasing order 3 < 2 < 1 according to H-bonding effect. This probably could be attributed to the conversion of superoxide radical ions into H(2)O(2), which leads to greater oxidative stress leading to apoptosis.

Cu(II) conjugation along the transformation of a vitamin K-3 derivative to a dinaphthoquinone methide radical - Badave, Kirti D.; Patil, Shalaka S.; Khan, Ayesha A.; Srinivas, Darbha; Butcher, Raymond J.; Gonnade, Rajesh G.; Puranik, Vedavati G.; Pinjari, Rahul V.; Gejji, Shridhar P.; Rane, Sandhya Y. (New Journal of Chemistry, 2014)
1,1'-Methide-bi-vitamin K-3 (B) has been isolated as a dinaphthoquinone methide radical (DNQM) by the transformation of 1-imino(acetylhydrazino)-vitamin K-3 (A). The transformation follows a biomimetic activation pathway mediated via Cu(II) ion catalyzed oxidative coupling. Single crystal X-ray and electron spin resonance (ESR) experiments combined with density functional calculations elucidate the ``resonance structure'' of the DNQM radical (B). Fluorescence investigations reveal that DNQM facilitates interaction with the cysteine residue. As compared to the parent substrate, B shows a depletion in the level of GSH, triggering apoptosis in HeLa cells.